Assessment and scaffolding in Master’s degree programmes: Implementation in the creation of a digital communication campaign - Godoy Martín, Francisco Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article addresses the implementation of scaffolding in an assessment process in a Master’s degree. Within the framework of digital communication, students were asked to create a campaign for an actual client: an animal protection association. Based on the implementation of participant observation as well as a survey conducted among students, this project demonstrates that scaffolding is effective in the context of a Master’s degree. Such results have been proven to be enhanced when scaffolding is combined with technology and the encouragement of professors.